Unfinished empire : the global expansion of Britain - Darwin, John (Bloomsbury Press, 2013)
The enormous influence of the British Empire cannot be escaped. It has shaped the world in countless ways, repopulating continents, carving out nations, imposing its language, technology and values. For perhaps two centuries its existence, expansion, and final collapse could be seen as the single largest determinant of historical events.